Investigating the Effects of ESL Learners’ Motivation and Anxiety on Task Based Language Teaching in Pakistan - Sameetah Fatima Malik; Azhar Pervaiz (Linguistics and Literature Review, 2023)
Motivation and anxiety play a significant role in the teaching and learning process, either  it is second language learning or Task Based Language Teaching (TBLT). The current research aimed to investigate the motivation and anxiety faced by Pakistani English as Second Language (ESL) learners while learning English language. A quantitative research design was used to conduct this research. Moreover, Structural Equation Modeling (SEM) was subsequently applied to record the relationship between task motivation and second language (L2) motivation, as well as to configure the association between task anxiety and foreign language anxiety. From two public sector colleges of Sargodha, eighty ESL learners participated in the experiment. They were shown a cartoon video and then they were asked to narrate the video in English. Furthermore, they were inquired about their task anxiety and task motivation. The results showed that task motivation has three sides, that is, positive attitude towards the task, negative attitude towards the task, and task diagnostic tool. Task anxiety construct also shows three sides-setting namely anxiety, language related anxiety, and anxiety reliefs. The results also revealed that TBLT is greatly affected by motivation and anxiety. The current study would help the teachers to gain knowledge about the motivational strategies used by their students. Lastly, the research would be helpful for ESL teachers to motivate their students and understand their anxieties. This study was limited to the video narration task. Hence, it is recommended to extend future studies by including more than one task while using a large sample size.